Pengelolaan Reklamasi Lahan Pascatambang Nikel di Sulawesi Tenggara Menggunakan Fitoremediasi (Studi Kasus: PT. X) - Savitri, Asri Ramadhani; Ipung Fitri Purwanti (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Law No. 3 of 2020 on Mineral and Coal Mining states that reclamation is an activity that must be carried out during mining operations in order to repair, restore and improve the quality of the environment and ecosystems so that they can function again according to their mission. Phytoremediation can serve as an alternative solution in reclamation activities that is cost effective, efficient and environmentally friendly. This research aims to determine the efficiency of nickel reduction using Sengon (Paraserianthes falcataria), while calculating and analysing the financial requirements and risk management involved. Nickel post-mining soil was placed in 25x25 cm polybags and four-month-old Sengon was planted. The plants were maintained with fertiliser and humic substances and watered daily. Nickel levels in the soil were measured using atomic absorption spectrophotometry (AAS). The results showed that reactor H0P0 (100% post-mining soil) successfully removed 72.5% of the nickel.